Semantic memory assesment - Ma. Macarena Martínez-Cuitiño; Virginia I. Jaichenco (Revista de Psicología, 2019)
Semantic memory stores information about objects’, words’ and the worlds’ meaning. This knowledge is impaired in patients with semantic dementia, Alzheimer’s disease and herpes encephalitis, among others. At least two different theoretical lines attempt to explain the organization of conceptual knowledge processing. The impairment of semantic information must be assessed with specifics tools in order to take in account the different aspects of its organization. The aim of this work is to review the different tasks that allow the assessment of semantic processing as well as indicating those that have been designed or adapted to be used in our population.